2020
DOI: 10.1186/s13065-020-00703-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular docking and molecular dynamic simulation studies of 2-chloro-5-[(4-chlorophenyl)sulfamoyl]-N-(alkyl/aryl)-4-nitrobenzamide derivatives as antidiabetic agents

Abstract: A series of 2-chloro-5-[(4-chlorophenyl)sulfamoyl]-N-(alkyl/aryl)-4-nitrobenzamide derivatives (5a-5v) has been synthesized and confirmed by physicochemical(R f , melting point) and spectral means (IR, 1 HNMR, 13 CNMR). The results of in vitro antidiabetic study against α-glucosidase indicated that compound 5o bearing 2-CH 3-5-NO 2 substituent on phenyl ring was found to be the most active compound against both enzymes. The electron donating (CH 3) group and electron withdrawing (NO 2) group on a phenyl ring h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…ADMET analysis of synthesized compounds was performed by Molinspiration online tool kit, OSIRIS property explorer and Pre ADMET online server [48][49][50].…”
Section: Pharmacokinetic Parametersmentioning
confidence: 99%
“…ADMET analysis of synthesized compounds was performed by Molinspiration online tool kit, OSIRIS property explorer and Pre ADMET online server [48][49][50].…”
Section: Pharmacokinetic Parametersmentioning
confidence: 99%
“…Format using open free software from Babel. The co-crystallised protein structures of CEBPD, TP73, ESR2, TAB1 and MAP3K5 of its PDB code 3L4W, 2XWC, 1U3Q, 5NZZ & 2CLQwas extracted from Protein Data Bank 1262 [32][33][34][35][36]. Together with the TRIPOS force eld, GasteigerHuckel (GH) charges were added to all designed derivatives for the structure optimization process.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…The American Diabetes Association classified diabetes into 2 major categories: Type 1 diabetes (T1D), caused by autoimmune destruction of the β-cell of the pancreas by producing specific antibodies against its cells, 1 and type 2 diabetes (T2D) as a result of a combination of resistance to insulin action and a secretory response by pancreatic β-cells that is inadequate to overcome insulin resistance, leading to relative insulin deficiency. 4 According to WHO data, more than 250 million people are currently living with diabetes, with this figure anticipated to rise to more than 592 million by 2035, 8 with T2D accounting for 80% to 90% of DM. 3 , 4 Astonishingly, a more significant percentage of people with DM are unaware that they have hyperglycemia until it gets to long-term hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…2 , 10 Management/treatment options for DM range from lifestyle modification, exercise, insulin injection, and use of anti-DM drugs. 5 , 11 The biochemical basis of most anti-DM drugs involves inhibiting the catalytic activities of carbohydrate metabolizing enzymes, such as human pancreatic α-amylase (HPA) and α-glucosidase, which reduces blood sugar levels by suppressing carbohydrate digestion and glucose uptake, 3 , 8 making them the primary targets in controlling blood glucose in DM patients. 12 - 14 Studies have shown that inhibition of HPA is a better suppressor of postprandial hyperglycemia (PPHG) than α-glucosidase because it prevents excessive accumulation of maltose.…”
Section: Introductionmentioning
confidence: 99%